2023
DOI: 10.3390/cancers15061892
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Nanoparticles-Based Radiotherapy in Cancer Treatment

Abstract: Radiation has been utilized for a long time for the treatment of cancer patients. However, radiotherapy (RT) has many constraints, among which non-selectivity is the primary one. The implementation of nanoparticles (NPs) with RT not only localizes radiation in targeted tissue but also provides significant tumoricidal effect(s) compared to radiation alone. NPs can be functionalized with both biomolecules and therapeutic agents, and their combination significantly reduces the side effects of RT. NP-based RT dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 211 publications
0
8
0
Order By: Relevance
“…The first one directly concerns MRI, which is an important imaging technology that provides non-invasive and accurate information about soft tissues, without the need for ionizing radiation or radiotracers. It has been reported that the accuracy of MR signals can be improved by using contrast agents containing several nanoparticles [174], particularly iron oxide nanoparticles, which have shown potential for early diagnosis of swelling and infection [175,176]. In another striking example, Gd-based liposomal MRI contrast agents have been used for targeted image-guided drug delivery.…”
Section: Cancer Theranosticsmentioning
confidence: 99%
“…The first one directly concerns MRI, which is an important imaging technology that provides non-invasive and accurate information about soft tissues, without the need for ionizing radiation or radiotracers. It has been reported that the accuracy of MR signals can be improved by using contrast agents containing several nanoparticles [174], particularly iron oxide nanoparticles, which have shown potential for early diagnosis of swelling and infection [175,176]. In another striking example, Gd-based liposomal MRI contrast agents have been used for targeted image-guided drug delivery.…”
Section: Cancer Theranosticsmentioning
confidence: 99%
“…Moreover, HT further sensitizes cancer cells to chemotherapy, having the advantages of minimal systemic toxicity. Some studies suggest that cancer stem cells are sensitized to radiation therapy by nanoparticle-mediated HT [ 117 ], while there is also evidence that hyperthermia can trigger immune-mediated responses in the cancer microenvironment [ 118 ].…”
Section: Future Applications and Challengesmentioning
confidence: 99%
“…Nevertheless, radiation alone is less effective due to the hypoxic microenvironment [ 25 ]. Nanoparticles have shown considerable promise in tumor radiation therapy, and their combination has the potential to improve the tumor’s lack of oxygen [ 26 ] and enhance the therapeutic effect. Wang et al developed pH-responsive functionalized nano-andrographic hydrogels coupled with 6-aminonicotinamide to inhibit the pentose phosphate pathway’s metabolism, thereby reducing NADPH production, inhibiting the conversion of oxidized glutathione to reduced glutathione, and enhancing sustained ROS production to increase radiotherapy sensitivity [ 27 ].…”
Section: Current Status Of Cancer Researchmentioning
confidence: 99%